Ni uno menos - Yimou, Zhang (Madrid Sony pictures, 2012)
In a remote mountain village, the teacher must leave for a month, and the mayor can find only a 13-year old girl, Wei Minzhi, to substitute. The teacher leaves one stick of chalk for each
Audio: Español, Mandarín con varios subtítulos
Writer: Xiangsheng Shi
Apta para todos los públicos
Minzhi Wei, Huike Zhang, Zhenda Tian
Keywords: Películas cinematográficas -- DVD